1990
DOI: 10.1002/hep.1840110622
|View full text |Cite
|
Sign up to set email alerts
|

Interaction Between Hepatitis B Surface Proteins and Monomeric Human Serum Albumin

Abstract: HBsAg is known to bind to human serum albumin polymerized by glutaraldehyde, human serum albumin has been found in preparations of HBsAg by several investigators. However, it is not yet known whether natural human serum albumin binds to hepatitis B virus under physiological conditions. We studied the binding between natural or recombinant HBsAg and monomeric human serum albumin by immunological, biochemical and biophysical methods. The binding capacity of 20-nm HBs spheres was variable but ranged up to six mol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0

Year Published

1991
1991
2010
2010

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(31 citation statements)
references
References 34 publications
1
30
0
Order By: Relevance
“…One possibility might be that the preS domains are covered in the blood by a serum protein partially protecting HBV from non-specific attachment to blood vessels. A number of serum proteins have been proposed for this function, including albumin (Krone et al, 1990) and apolipoprotein H (Mehdi et al, 1996;Stefas et al, 2001). In a recent publication, Deng et al (2007) propose lipoproteinlipase (LPL) as a binding factor for the preS1 domain.…”
Section: Discussionmentioning
confidence: 99%
“…One possibility might be that the preS domains are covered in the blood by a serum protein partially protecting HBV from non-specific attachment to blood vessels. A number of serum proteins have been proposed for this function, including albumin (Krone et al, 1990) and apolipoprotein H (Mehdi et al, 1996;Stefas et al, 2001). In a recent publication, Deng et al (2007) propose lipoproteinlipase (LPL) as a binding factor for the preS1 domain.…”
Section: Discussionmentioning
confidence: 99%
“…26,27 This binding site has been 133, and 131 and 133, as found in cases 3 and 4, respectively, have not been described previously, so the signifthought to be located between amino acids 17 and 28 in the pre-S2 region. 28 Therefore, the finding that nu-icance of these observations are still unclear. However, it has been demonstrated that amino acid changes at cleotide deletions in the pre-S2 region partially overlap the binding site for glutaraldehyde cross-linked human codons 124, 129, 131, 137, 140, and 145 31 and at codons 126, 131, 132, and 145 34 were identified in liver transserum albumin in case 4 suggested that this mutant may have lower infectivity than wild-type particles.…”
Section: 10mentioning
confidence: 99%
“…HBsAg can be present at concentrations ranging from 1 g/ml to over 1000 g/ml in the serum of patients who are chronically infected with HBV (15). HBsAg has been shown to bind to some forms albumin (16), and therefore it could potentially be retained on the column through this interaction.…”
Section: Potential Retention Of Albumin-related and Albuminbinding Prmentioning
confidence: 99%